Analisis kualitas Produk, Variasi Produk, dan Suasana Toko Terhadap Minat Beli Ulang Pada Konsumen Mie Gacoan Krian Sidoarjo - Moch Fani Andrian; Lilik Indayani; Muhammad Yani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Business competition in the current era is increasingly fierce, especially in the food business sector, companies are continually required to survive and continue to excel in the competition. Repurchase interest is one of the factors that influences a company to gain profits and survive. The object of this research is Mie Gacoan Krian Sidoarjo. Mie Gacoan is a spicy noodle restaurant that is popular and widely known among the public today, especially among young people. This research aims to analyze product quality, product variety and shop atmosphere on repurchase interest among Mie Gacoan consumers. This research method uses quantitative methods with primary data types. The respondents in this research were consumers of Mie Gacoan Krian Sidoarjo. This research was determined using the formula from Lemeshow, namely 96 people were obtained. The technique for taking data analysis uses multiple linear analysis methods and then processed using the SPSS application program. The results of this research show that; Product Quality has a significant positive effect on Repurchase Intention; Product Variation has a significant positive effect on Repurchase Intention; Store atmosphere has a significant positive effect on repurchase interest. Keywords: Product Quality, Product Variety, Store Atmosphere, Repurchase Intention